CLASSROOM TEACHERS’ STRATEGY IN BUILDING CHARACTER VALUE FOR ELEMENTARY STUDENTS IN SIAK DISTRICT - Dwi Bella Lestari; Siti Quratul Ain (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Building character value is objective because character is a must and essential for teachers to apply. The teacher's strategy in building character values basically influences the level of understanding, practice, and awareness of students in practicing the values. The formulation of the problem is how the classroom teacher's strategy instills students’ character values. The research objective is to find out the teacher's strategy in building the students’ character values. The research is field research with a qualitative approach at SDN 014 Teluk Mesjid in Siak. Data collection techniques are observation, interviews, and documentation by using descriptive qualitative methods. The research results indicate that the classroom teacher already has a strategy for building character values in terms of educational aspects directly through example, encouragement, practice, competition, and habituation, as well as indirectly through prohibitions, supervision, and punishment. The culture and environment in SDN 014 Teluk Mesjid Siak Regency influence the addition of students’ character values. Culture and organizational environment are deeply attached to an institution, such as greeting as habits, respecting elders, not cheating, being honest, and so on. Nevertheless, there is an unfortunate thing in the case of students who are still negligent in carrying out and applying several cultural character values with light punishment from the school. Suggestions of the research are intended